2008
DOI: 10.1073/pnas.0712387105
|View full text |Cite
|
Sign up to set email alerts
|

Association of guanine nucleotide-exchange protein BIG1 in HepG2 cell nuclei with nucleolin, U3 snoRNA, and fibrillarin

Abstract: Antibodies against BIG1 or nucleolin coprecipitated both proteins from nuclei, which was abolished by the incubation of nuclei with RNase A or DNase, indicating that the interaction depended on nucleic acids. 32 P labeling of RNAs immunoprecipitated with BIG1 or nucleolin from nuclei revealed bands of Ϸ210 bases that also hybridized with U3 small nucleolar (sno)RNA-specific oligonucleotides. Clones of U3 snoRNA cDNAs from the material precipitated by antibodies against BIG1 or nucleolin yielded identical nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…ARF guanine-nucleotide exchange factors such as BRAG2 have been detected in nuclei both biochemically and morphologically (Dunphy et al, 2007). Moreover, both BIG1, a guanine-nucleotide exchange factor that is localized to the trans-Golgi network at steady state, and Centaurin a1, a GTPase-activating protein for ARF6, have been reported to enter the nucleus and interact with the nucleolar protein nucleolin (Dubois et al, 2003;Padilla et al, 2008). Similarly, PIKE (AGAP2/Centaurin-g1) was also found within nuclei (Dunphy et al, 2007).…”
Section: Discussionmentioning
confidence: 91%
“…ARF guanine-nucleotide exchange factors such as BRAG2 have been detected in nuclei both biochemically and morphologically (Dunphy et al, 2007). Moreover, both BIG1, a guanine-nucleotide exchange factor that is localized to the trans-Golgi network at steady state, and Centaurin a1, a GTPase-activating protein for ARF6, have been reported to enter the nucleus and interact with the nucleolar protein nucleolin (Dubois et al, 2003;Padilla et al, 2008). Similarly, PIKE (AGAP2/Centaurin-g1) was also found within nuclei (Dunphy et al, 2007).…”
Section: Discussionmentioning
confidence: 91%
“…Later experiments with recombinant proteins in vitro demonstrated that GEP activity of BIG1 was decreased after phosphorylation by PKA (12). Most recently, it was reported that BIG1, nucleolin, U3 small nucleolar RNA, the U3-binding protein fibrillarin, and the RNA-binding protein La may exist together in nuclear complexes, consistent with a potential role for BIG1 in nucleolar function (13). The C-terminal region of BIG1 includes a binding site for myosin IXb.…”
mentioning
confidence: 81%
“…Cell immunofluorescence was imaged using a confocal fluorescence microscope (LSM 510, Zeiss) as previously described. 18 necessary but not enough for the binding. These new insights into the conformational propensities of 14-3-3 proteins and intrinsically disordered partners reveal that other structural clues (e.g., anchor-type residues) need to be identified to understand their interactions.…”
mentioning
confidence: 98%